2008
DOI: 10.1097/mph.0b013e318180bbc9
|View full text |Cite
|
Sign up to set email alerts
|

Late Side Effects of High-dose Steroid Therapy on Skeletal System in Children With Idiopathic Thrombocytopenic Purpura

Abstract: Corticosteroids have been widely used in the treatment of idiopathic thrombocytopenic purpura (ITP). We evaluated the late side effects of high-dose methylprednisolone (HDMP) therapy on bone metabolism in children with ITP. Twenty-eight children with acute ITP treated with HDMP (30 mg/kg/d for 3 d then 20 mg/kg/d for 4 d) and 28 controls were enrolled in the study. Bone mineral density (BMD), urinary calcium creatinine ratio, urinary levels of deoxypyridinoline, serum levels of calcium, phosphate, parathyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Our systematic review identified four case series or case‐control studies of between 24 and 36 children and one adult series of 18 patients assessing BMD after steroids (Table SI). In children, there was a significant negative correlation between BMD and cumulative steroid dose (Dilber et al , ; Yildirim et al , ; Tantawy et al , ). In one series, 9/36 (25%) children had osteopenia (BMD Z‐score ≤1) and one had osteoporosis (BMD Z‐score ≤−2 plus a clinically significant fracture) (Tantawy et al , ).…”
Section: Impact Of Glucocorticoids In Patients With Itpmentioning
confidence: 99%
“…Our systematic review identified four case series or case‐control studies of between 24 and 36 children and one adult series of 18 patients assessing BMD after steroids (Table SI). In children, there was a significant negative correlation between BMD and cumulative steroid dose (Dilber et al , ; Yildirim et al , ; Tantawy et al , ). In one series, 9/36 (25%) children had osteopenia (BMD Z‐score ≤1) and one had osteoporosis (BMD Z‐score ≤−2 plus a clinically significant fracture) (Tantawy et al , ).…”
Section: Impact Of Glucocorticoids In Patients With Itpmentioning
confidence: 99%
“…Steroidler birçok farkl› klinik durumda tedavi amac›yla kullan›l-maktad›r. Steroidlerin iskelet sistemine direkt ve indirekt etkileri bilinmektedir (2). Kortikosteroidler osteoblastlar›n replikasyonu, diferansiasyonu ve fonksiyonlar›n› bozar ve olgun osteoblast ve osteositlerin apopitoza gitmelerine neden olarak kemik kayb›n› art›r›rlar.…”
Section: G Gi Ir Ri Ifl Flunclassified
“…Kortikosteroidler osteoblastlar›n replikasyonu, diferansiasyonu ve fonksiyonlar›n› bozar ve olgun osteoblast ve osteositlerin apopitoza gitmelerine neden olarak kemik kayb›n› art›r›rlar. Kortikosteroidlere ba¤l› osteonekroz mekanizmas› tam olarak anlafl›lmam›fl olsa da farkl› çal›flmalarda bu kemik kayb›n›n nekroza neden olabilece¤i belirtilmifltir (2,3). Bununla birlikte steroid kullan›m›na ba¤l› olarak adiposit say›s›nda ve büyüklü-¤ünde art›fl kemik ili¤inde yer de¤ifltirmeye neden olmaktad›r.…”
Section: G Gi Ir Ri Ifl Flunclassified
“…In many cases, the exact mechanism of ON is unknown; however, in nontraumatic ON, the pathogenesis is believed to involve vascular compromise, bone and cell death, or defective bone repair (1). Corticosteroid use has often been indicated as a cause of ON (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16); however, again this has most commonly affected the femoral head. Bisphosphonates have also been implicated as a cause of ON, with most published data pointing to its manifestation in the jaw (7,17).…”
mentioning
confidence: 99%